Modulation of oxazolone-induced hypersensitivity in mice by selective PDE inhibitors - I. Moodley; Y. Sotsios; B. Bertin (Mediators of Inflammation)
The effects of PDE inhibitors on oxazolone-induced contact hypersensitivity (CS) were studied in mice. Rolipram, Ro 20-1724 and theophylline dose dependently inhibited CS but none caused >53% inhibition. ED30 values at 24 h before challenge for rolipram, Ro 20-1724 and theophylline were 2.1, 5.4 and 30.4 mg/kg, p.o., respectively. Milrinone and SKF 94836 at 30 mg/kg caused a small, but significant inhibition of 13% and 18%, respectively, although the inhibition (8%) caused by zaprinast was not significant. Betamethasone (10 mg/kg, p.o.) caused a marked inhibition (80%) as did indomethacin (65% at 5 mg/kg, p.o.). Rolipram and Ro 20-1724 inhibited proliferation of mouse lymphoblasts with IC50 values of 0.08 μM and 0.83 μM, respectively. In contrast, zaprinast caused only a weak inhibition (IC50 = 119 μM) of lymphocyte proliferation, whereas SKF 94836 and theophylline failed to cause any significant inhibition at 100 μM (26% and 2%, respectively). These findings suggest that PDE IV isozymes play a principal role in mediating CS by inhibiting lymphocyte activation.